On Kolmogorov-Type Inequalities Taking into Account the Number of Changes in the Sign of Derivatives - Kofanov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For 2π-periodic functions \(x \in L_\infty ^r \) and arbitrary q ∈ [1, ∞] and p ∈ (0, ∞], we obtain the new exact Kolmogorov-type inequality \(|| x^(k) ||_q \leqslant (\frac{v(x^(k))}{2})^{1/q} \frac{|| \phi_{r-k} ||_q}{||| \phi_r |||_p^\alpha} ||| x |||_p^\alpha || x^(r) ||_\infty^{1- \alpha}, k, r \in N, k < r,\) which takes into account the number of changes in the sign of the derivatives ν(x (k)) over the period. Here, α = (r − k + 1/q)/(r + 1/p), ϕ r is the Euler perfect spline of degree r, \(\begin{gathered} \left\| {\left| x \right|} \right\|_p : = {\text{sup}}_{a,b \in {\text{R}}} \{ E_0 (x)_{L_p [a,b]} :x'(t) e 0{\text{ }}\forall t \in (a,b)\} , \\ {\text{ }} \\ {\text{ }}E_0 (x)_{L_p [a,b]} : = {\text{ inf}}_{c \in {\text{R}}} \left\| {x - c} \right\|_{L_p [a,b]} , \\ \\ \left\| x \right\|_{L_p [a,b]} : = \left\{ {\int\limits_a^b {\left| {x(t)} \right|^p dt} } \right\}^{1/p} {\text{ for }}0 < p < \infty , \\ \end{gathered} \) and \(\left\| x \right\|_{L_p [a,b]} : = {\text{ sup vrai}}_{t \in \left[ {a,b} \right]} \left| {x(t)} \right|\) . The inequality indicated turns into the equality for functions of the form x(t) = aϕ r (nt + b), a, b ∈ R, n ∈ N. We also obtain an analog of this inequality in the case where k = 0 and q = ∞ and prove new exact Bernstein-type inequalities for trigonometric polynomials and splines.